Preparation of organic fertilizers by means of two composting techniques in markets of the canton la Troncal - Arizaga Gamboa, Raúl Enrique; Balladares Montero, Julio César (SATHIRI, 2021)
The current research work was carry out in the canton La Troncal province of Cañar, it is intended to analyze the best treatment of organic waste in the Mercado Central and Abdon Calderon, these Mercado generate some average tree tons daily of waste to be reused and transformed in organic fertilizers; there are for the information was unloaded. Two techniques were analyzed respectively for the use of waste a that are Bocashi and Humus of lombriz also physical parameters such as pH and temperature. The techniques were developed obtaining as a result that by taking advantage of organic waste and processing into fertilizers. The Bocashi fertilizer is the best option for canton La Troncal with base in the results obtained in the analyses for Nitrogen, Phosphorous and Potassium of the technique were obtained
Keywords: Fertilizer; Organic Waste; Transformation; Bocashi; Humus of lombriz